Expression Profile and Subcellular Localization of GAPDH in the Smooth Muscle Cells of Human Atherosclerotic Plaque: An Immunohistochemical and Ultrastructural Study with Biological Therapeutic Perspectives. (23rd May 2014) - Perrotta, Ida; Aquila, Saveria; Mazzulla, Sergio
Abstract: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) has long been considered a classical glycolytic enzyme involved exclusively in cytosolic energy production. Several recent studies, however, have demonstrated that GAPDH is a multifunctional protein whose presence and activity can be regulated by disease states and/or experimental manipulation. Expression levels of GAPDH have been shown to be altered in certain tumors as well as in proliferating and differentiating cells. Since dedifferentiation and proliferation of smooth muscle cells (SMCs) are important features of human atherosclerosis, we have characterized the expression profile of GAPDH in the SMCs of atherosclerotic plaques and its putative interrelationship with the synthetic/proliferative status of these cells utilizing the proliferating cell nuclear antigen (PCNA) antibody, a valuable marker of cell proliferation. Western blot data revealed that GAPDH was significantly upregulated in atherosclerotic plaque specimens. Immunohistochemical stains demonstrated that GAPDH accumulated in the nucleus of dedifferentiated SMCs that also showed positive immunoreactivity for PCNA, but remained cytoplasmatic in the contractile SMCs (PCNA-negative), thus reflecting the proliferative, structural and synthetic differences between them. We suggest that, in human atherosclerotic plaque, GAPDH might exert additional functions that are independent of its well-documented glycolytic activity and might play key roles in development of the disease.